Three facets of public health and paths to improvements : behavior, culture, and environment - Fiedler, Beth Ann (Academic Press, 2020)
"Provides an overview on how specific indicators like environment, culture and behavior play a role in developing improved outcomes for public health in local, regional, national and global health policy and concerns."--Publisher